Analysis of macro- and Microminerals Content in the Einkorn (Triticum monococcum L.) Samples Cultivated in Kastamonu, Turkey - Turhan, Şeref; Kurnaz, Aslı (Turkish Science and Technology Publishing (TURSTEP), 2021)
Wheat is an important cereal product because of its nutritional value, economy, culture, and history. Einkorn (Triticum monococcum L.) assumed as the oldest wheat. Einkorn locally called “siyez” has recently become popular as a super grain with the thought of being very nutritious in Turkey. In this study, the contents of macrominerals (Na, Mg, Ca, and K) and microminerals (Cr, Cu, Fe, Mn and Zn) in twenty-one einkorn samples collected from different cultivation areas in Kastamonu were determined by using an inductively coupled plasma-optical emission spectrometry following microwave-assisted acid digestion. The results were compared with those analyzed in einkorn and other wheat types in the literature. Average concentrations of K, Ca, Mg, Na, Fe, Zn, Mn, Cr and Cu analyzed in einkorn samples were found as 3712, 1303, 656, 53, 167, 34, 29, 0,7 and 0,6 mg kg-1, respectively. The literature comparison revealed that the investigated einkorn samples were richer in terms of Ca and Fe contents compared to einkorn, emmer, spelt, buckwheat, and durum wheat samples grown in our country and different countries.
Keywords: S; Agriculture (General); Agriculture; kastamonu (turkey); icp-oes; S1-972; einkorn; microminerals; siyez; macrominerals; 2. Zero hunger